Strengthening the Acceleration of Digital Transformation in Developing a Digital Economy Curriculum - Tiwow, Gilly Marlya; Rawis, Joulanda A.M.; Lengkong , Jeffry Sony Junus; Rotty, Viktory Nicodemus Joufree (International Journal of Information Technology and Education, 2023)
This study aims to analyze and identify effective strategies to accelerate digital transformation in developing digital economy curricula. Digital transformation has brought significant changes in various sectors, including the economic sector. In the context of education, curriculum development that is responsive to the needs of the digital economy is crucial in preparing students to face the demands of the ever-evolving world of work. This study will use qualitative and quantitative approaches to collect and analyze data. Through a comprehensive literature review, this research will identify best practices in digital economy curriculum development in various educational institutions. Furthermore, this research will conduct interviews with key stakeholders, such as educators, digital industry representatives, and education experts, to gain an in-depth understanding of the challenges and opportunities associated with digital transformation in developing digital economy curricula. The collected data will be analyzed using qualitative methods such as content analysis and thematic analysis, as well as quantitative methods such as descriptive statistics and factor analysis. This analysis will provide in-depth insight into the factors that influence the success of digital transformation in digital economy curriculum development, including challenges, training needs, available resources, and effective implementation strategies. The results of this study are expected to provide recommendations for education policymakers, curriculum developers, and educational institutions to strengthen their efforts in implementing digital transformation in developing digital economy curricula. It is also hoped that this research can contribute to our understanding of how digital economic education can prepare future generations to become competitive actors in the digital era.